2021
DOI: 10.1002/pc.26205
|View full text |Cite
|
Sign up to set email alerts
|

In situ growth of TiO2 nanoparticles onto PBO fibers via a mussel‐inspired strategy for enhancing interfacial properties and ultraviolet resistance

Abstract: In this work, to overcome the poor interfacial adhesion and ultraviolet (UV) resistance of poly(p-phenylene benzobisoxazole) (PBO) fiber simultaneously, a new hierarchical reinforcement was fabricated by in situ growing titanium dioxide (TiO 2 ) nanoparticles on the surface of the fiber using musselinspired polydopamine (PDA) as a robust reaction platform. The surface morphologies and chemical compositions of the modified fiber were measured to prove the TiO 2 binding. The interfacial shear strength of PBO fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…27 The PBO-Fe-PDA fibers showed a new absorption peak at 3183 cm À1 and a broad peak at 3400 cm À1 corresponding to the stretching vibration of NH 2 and -OH of catechol in PDA, respectively, which proved that PDA was successfully grafted to the PBO-Fe fibers. 4,28 This supported the SEM findings and demonstrated that PDA was effectively grafted on the PBO-Fe fibers. Compared to unaged PBO fibers, PBO fibers after 288 hours of UV exposure displayed two peaks at 1718 and 1734 cm À1 (Figure 3(c)), which can be attributed to oxazole ring breaking and the creation of amide bonds in PBO fibers under UV radiation.…”
Section: Resultssupporting
confidence: 77%
“…27 The PBO-Fe-PDA fibers showed a new absorption peak at 3183 cm À1 and a broad peak at 3400 cm À1 corresponding to the stretching vibration of NH 2 and -OH of catechol in PDA, respectively, which proved that PDA was successfully grafted to the PBO-Fe fibers. 4,28 This supported the SEM findings and demonstrated that PDA was effectively grafted on the PBO-Fe fibers. Compared to unaged PBO fibers, PBO fibers after 288 hours of UV exposure displayed two peaks at 1718 and 1734 cm À1 (Figure 3(c)), which can be attributed to oxazole ring breaking and the creation of amide bonds in PBO fibers under UV radiation.…”
Section: Resultssupporting
confidence: 77%
“…As a new coating material, PDA contains rich catechol groups, has excellent self-adhesion, and can interact with many groups. 26 Compared with the conventional impregnation method, the FIP method can reduce the polymerization rate of PPy, effectively avoid adverse cross-linking or branching of the polymer, and make the PPy coating more uniform and dense, improving electrical conductivity. 27 At the same time, there is also a conjugated system between PDA and PPy, which can enhance the intermolecular attraction through π−π packing.…”
Section: Resultsmentioning
confidence: 99%
“…Figure S4a–c showed the surface microstructure of TTS yarns, TTS@PDA yarns, and TTS@PDA@PPy yarns, respectively. As a new coating material, PDA contains rich catechol groups, has excellent self-adhesion, and can interact with many groups . Compared with the conventional impregnation method, the FIP method can reduce the polymerization rate of PPy, effectively avoid adverse cross-linking or branching of the polymer, and make the PPy coating more uniform and dense, improving electrical conductivity .…”
Section: Resultsmentioning
confidence: 99%
“…[ 20 ] Surface grafting and coating can improve the surface reactivity and roughness of PBO fibers, and will also damage the intrinsic mechanical strength to a certain extent. [ 21‐22 ] Meanwhile, the new interfaces introduced would bring adverse effect on the mechanical properties and wave‐ transparent performances of the laminated composites. [ 23 ]…”
Section: Background and Originality Contentmentioning
confidence: 99%